Breeding biology and mating system of Brown Accentors Prunella fulvescens on the Tibet Plateau. Issue 2 (2nd April 2020) - Huang, Ji; Liu, Jinlong; Li, Guopan; Yan, Han; Li, Shaobin
ABSTRACT: Capsule: The mating system of the Brown Accentor Prunella fulvescens in the high altitudes of the Tibeta plateau is mainly monogamous but polyandry was recording in 9.7% of breeding groups. Aims: To describe the poorly known breeding biology of Brown Accentors in the high-altitude environment of the northeastern Tibet plateau. Methods: Individually colour-ringed birds were observed during two breeding seasons. Biometrics were recorded for breeders, and reproductive variables were quantified. Results: Brown Accentors were territorial during the breeding season and were resident year-round. Most groups (90.3%, n  = 31 groups) were socially monogamous and the remainder (9.7%) were polyandrous, with two males sharing a female's territory. Mean group size was 2.1 adults and the population adult sex ratio was 52% male. The birds raised a single brood during the breeding season. Nests were invariably located in Sea Buckthorn Hippophae rhamnoides . Eggs were laid between late June and late July, and mean clutch size was 3.4 ± 0.6 (SD) eggs. Incubation was undertaken by the female and lasted 12.9 ± 0.9 (SD) days. Both sexes provisioned young in the nest for 13.9 ± 1.2 (SD) days. Females provided significantly more feeding visits than did males. Brood size at estimated fledging dates averaged 2.2 ± 0.7 (SD) nestlings. Forty-five per cent of nesting attempts ( n  = 37) fledged at least one nestling. Conclusions: Like other species in the family Prunellidae, the Brown Accentor exhibits remarkable variation in its mating system.